Study of Karangpilang II Water Production Quality Control Using Statistical Process Control (SPC) - Neneng Amel Hizni’am; Nieke Karnaningroem; Mas Agus Mardyanto (IPTEK Journal of Proceedings Series, 2019)
IPAM Karangpilang’s water quality has fluctuated and there are several parameters whose quality is not in accordance with the quality standard. Therefore, IPAM Karangpilang II needs to carry out quality control to maintain the quality of drinking water products according to the applicable quality standards. This research aims to analyze the application of the quality control system for drinking water products at IPAM Karangpilang II and look for the causes of decreasing production water quality at IPAM Karangpilang II. So that alternative improvements can be determined to maintain drinking water quality at IPAM Karangpilang II. Quality control method in this study using Statistical Process Control (SPC). Analysis were using primary data on drinking water quality starting from March to April 2019. Measurement parameters used include pH, Total Dissolved Solid (TDS), Turbidity, and Organic matter. Determination of a process controlled using control chart and then implemented using a fishbone diagram to determine the factors that result in decreased production of water quality. Control charts are in a statistically uncontrolled condition on the pH parameters in the clearator and filter units, Total Dissolved Solid (TDS) parameters on the clearator unit, turbidity parameters in the pre-sedimentation unit, clearator and filter, and organic matter parameters in pre-sedimentation and filter units. While in the production of water control chart in a state of uncontrolled statistically in the turbidity. Based on the fishbone diagram, factors that cause the control chart to be in an uncontrolled condition are that the overflow rate clearator does not appropriate with design criteria, technical errors such as clogging of the tube settler on the clearator, congestion coagulant pump stagnation, tube settler replacement in the clearator, seldom using coagulant dosage , decrease in the quality of raw water in the parameters of organic matter and raw water conditions that fluctuate due to the rainy season